Onsite Non-potable Reuse for Large Buildings: Environmental and Economic Suitability as a Function of Building Characteristics and Location - Arden, Sam (Water Res, 2020)
Onsite non-potable reuse (NPR) is a way for buildings to conserve water using onsite sources for uses like toilet flushing, laundry and irrigation. Although early case study results are promising, aspects like system suitability, cost and environmental performance remain difficult to quantify and compare across broad geographic contexts and variable system configurations. In this study, we evaluate four NPR system types – rainwater harvesting (RWH), air-conditioning condensate harvesting (ACH), and source-separated graywater and mixed wastewater membrane bioreactors (GWMBR, WWMBR, respectively) – in terms of their ability to satisfy onsite non-potable demand, their environmental impacts and their economic cost. As part of the analysis, we developed the Non-potable Environmental and Economic Water Reuse Calculator (NEWR), a publicly available U.S. EPA web application that allows users to generate planning-level estimates of system cost and environmental performance using location and basic building characteristics as input. By running NEWR for a range of scenarios, we find that, across the U.S., rainfall and air-conditioner condensation are only able to satisfy a fraction of the non-potable demand typical of large buildings even under favorable climate conditions. Environmental impacts of RWH and ACH systems also depend on local climate and were found to be competitive to MBR systems where annual rainfall exceeds approximately 10 in/yr or annual condensation potential exceeds approximately 3 gal/cfm. MBR systems can meet all non-potable demands but their environmental impacts depend more on the composition of the local energy grid, owing to their greater reliance on electricity inputs. Incorporation of thermal recovery to offset building hot water heating requirements amplifies this dependence, with mixed results depending on grid composition and whether thermal recovery offsets natural gas or electricity consumption. Additional environmental benefits are realized when NPR systems are implemented in water scarce regions with diverse topography and regions relying on groundwater sources, which increases the benefits of reducing reliance on centralized drinking water services. In terms of cost, WWMBRs were found to be the most cost-competitive, achieving cost parity with local drinking water rates in 10% of surveyed cities.